Use of a Tracheal Tube as a Nasally Inserted Supraglottic Airway in a Case of Near-Fatal Airway Obstruction Caused by Epiglottitis - Masayuki Ozaki; Koji Murashima (Case Reports in Anesthesiology)
Airway management is critical during near-fatal obstruction of the upper airway in epiglottitis; however, this is challenging because of the sitting posture and agitated mental status of the patient. Moreover, there is currently no established protocol for safe airway management in patients with epiglottitis. Here, we describe the use of a conventional tracheal tube as a nasolaryngeal airway to maintain airway patency at the site of airway narrowing in the supine position, which enabled alleviation of imminent airway obstruction in a patient with epiglottitis. For definitive airway establishment, tracheostomy was then safely performed in the supine position.